PROBLEMS OF REHABILITATION TREATMENT OF SERVICEMEN AND CIVILIANS HAVE SUFFERED IN EMERGENCIES - T. I. Kabakova; V. V. Gatsal (Фармация и фармакология (Пятигорск), 2015)
Especially the provision of pharmaceutical care to servicemen and civilian victims of terrorist acts, are studied in terms of rehabilitation treatment on the example of the branch "Pyatigorsk" sanatorium resort "The North" of the Ministry of Defense. Sanatorium treatment of persons with traumatic lesions of the nerve root and plexus is a complex that includes spa therapy in the form of baths, mud, mineral water and medicines for the relief of pain. With limited financing a number of problems that require solutions for high-quality medical and psychological rehabilitation of victims in emergency situations. According to a study developed regulations on the organization of nursing and pharmacy functional staff responsibilities due to changes in the scope and con-tent of their work duties in the present conditions